Three new species of Micropsalliota (Agaricaceae, Basidiomycota) from central and southern Vietnam - Ivanova, Daria; Morozova, Olga; Pham, Thi Ha Giang (Phytotaxa, 2023)
Data on the species diversity of the genus Micropsalliota in Vietnam is still insufficient. In the current paper, three new species with small basidiomata (M. appendiculata, M. inflata, and M. suricatoides) are collected from Dong Nai and Gia Lai provinces of Vietnam, and identified based on morphological and molecular data. Micropsalliota appendiculata is characterized by an appendiculate margin of pileus, M. inflata – by red pileus and inflated pileipellis hyphae cells, and M. suricatoides possesses beige pileus with brown fibrils and stipitipellis hyphae with capitate apices. The study is provided with photographs of basidiomata, illustrations, descriptions of macro- and micromorphological features, and phylogenetic trees to show the position of the three new species. Discussion on similar taxa is also given.